2010
DOI: 10.1007/s10554-010-9711-3
|View full text |Cite
|
Sign up to set email alerts
|

Coronary to pulmonary artery fistula: morphologic features at multidetector CT

Abstract: The objective of this study is to evaluate the incidence and morphologic features of coronary-pulmonary artery fistulas (CPAF) by multidetector computed tomography (MDCT). From 2006 to 2008, 5,372 patients underwent ECG-gated cardiac CT scans using 64-slice MDCT at our institute. Among them, 17 cases of CPAF were detected (M:F = 14:3, mean age = 63 years). Chief complaints of patients were chest pain (n = 12), abnormal cardiac test (n = 3), known coronary artery disease (n = 1), and known CPAF (n = 1). We retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 15 publications
6
55
2
1
Order By: Relevance
“…This discrepancy with cardiac catheterization could have resulted from the difference in the modality used. In our study, 67% of CPAFs originated from both the right and left coronary arteries, which is in accordance with previous studies using CT (53-59%) (16)(17)(18)(19). The remaining 33% of CPAFs in our study originated from a single coronary artery; 25% of CPAFs originated from the LCA and 8% of CPAFs originated from the RCA.…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy with cardiac catheterization could have resulted from the difference in the modality used. In our study, 67% of CPAFs originated from both the right and left coronary arteries, which is in accordance with previous studies using CT (53-59%) (16)(17)(18)(19). The remaining 33% of CPAFs in our study originated from a single coronary artery; 25% of CPAFs originated from the LCA and 8% of CPAFs originated from the RCA.…”
Section: Discussionsupporting
confidence: 92%
“…CTCA not only can demonstrate the complex anatomy non-invasively, but also it is easy to do the follow-up studies. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [13] reported a 0.32% prevalence of CPAF, based on their finding of 17 CPAF cases in 5372 patients. Yun et al [14] reported 29 CPAF cases in 6624 patients who underwent CTCA, resulting in an even higher prevalence of 0.44%.…”
Section: Epidemiologymentioning
confidence: 99%